2011
DOI: 10.1021/la104400m
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Magnetic Field Distribution on the Micrometer Scale and Generation of Magnetic Bead Patterns for Microfluidic Applications

Abstract: As is well known, controlling the local magnetic field distribution on the micrometer scale in a microfluidic chip is significant and has many applications in bioanalysis based on magnetic beads. However, it is a challenge to tailor the magnetic field introduced by external permanent magnets or electromagnets on the micrometer scale. Here, we demonstrated a simple approach to controlling the local magnetic field distribution on the micrometer scale in a microfluidic chip by nickel patterns encapsulated in a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 47 publications
0
48
0
1
Order By: Relevance
“…The SPMBs with carboxyl groups were functionalized with C DNA according to our previous reports (He et al 2014; Yu et al 2011; Yu et al 2014; Yu et al 2013). Briefly, 40 μL of 50.0 mg/mL SPMBs were first washed three times with MES buffer (50.0 mM MES, pH = 6.0).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPMBs with carboxyl groups were functionalized with C DNA according to our previous reports (He et al 2014; Yu et al 2011; Yu et al 2014; Yu et al 2013). Briefly, 40 μL of 50.0 mg/mL SPMBs were first washed three times with MES buffer (50.0 mM MES, pH = 6.0).…”
Section: Methodsmentioning
confidence: 99%
“…Magnetic beads have been widely used in biological sample preparation and detection assays due to their benefits of large surface-to-volume ratio, easy manipulation, flexible functionalization, and excellent biocompatibility (Chen et al 2010; Yu et al 2011; Yu et al 2014; Yu et al 2013). Owing to the ease of separation and enrichment of the targets, magnetic beads were widely used to improve the selectivity and sensitivity of various analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the interaction on the ZnO nanorod surface, herringbone structures were incorporated inside the microfluidic device for enhanced mixing . Highly selective detection of H5N2 subtype AIV is achieved by fast continuous flow in the microfluidic channels that effectively minimizes nonspecific adsorption . The entire detection process could be completed within 1.5 h, while the limit of detection (LOD) for the H5N2 AIV was measured as 3.6 × 10 3 EID 50 mL −1 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, magnetic particles as induced by a magnetic field can self-assemble, resulting in a 1D, 2D or 3D structure and morphology [1][2][3][4]. It has been reported that self-assembled materials with 3D structures demonstrate more remarkable application prospects in magnetic recording devices, optoelectronic devices, biological sensors, etc.…”
Section: Introductionmentioning
confidence: 99%